Toward a New Political Praxis for Trumpamerica: New Directions in Critical Race Theory. (November 2019) - Bonilla-Silva, Eduardo
The election of 45 brought significant questions about race (and race-class) that merit theoretical consideration. My goal in this article is to discuss how racial theory applies to three main themes that followed the 2016 election: (a) dealing with the "racists"?, (b) the anxieties of the poor and white working class, and (c) hegemonic racism in Trumpamerica. I also briefly outline where I think racial theory needs to develop to combat racism in Trumpamerica.